Pengaruh Green HRM Practices dan Self-Efficacy terhadap Environmental Performance melalui Green Innovation pada Karyawan Milenial Perbankan di Jakarta Barat - Marlina Melani Putri; Netania Emilisa; Johan Frederick Sanger; Adil Qusai; Saiben Pacaambang (OPTIMAL Jurnal Ekonomi dan Manajemen, 2025)
This study aims to examine the influence of Green Human Resource Management (GHRM) Practices and Self-Efficacy on the Environmental Performance of millennial employees in the banking sectorJakarta Barat, with Green Innovation as a mediating variable. As the dominant workforce today, millennials play a crucial role in supporting organizational sustainability. This research uses a quantitative approach through a survey of millennial employees in several banking institutions. The findings show that Green HRM Practices and Self-Efficacy have a positive and significant effect on Environmental Performance. Furthermore, Green Innovation is proven to mediate the relationship between these variables and environmental performance. These results suggest that environmentally focused HR policies and strong employee self-belief can drive green innovation, which in turn enhances environmental performance. The practical implication of this research encourages banking institutions to strengthen GHRM practices and foster a work culture that supports green innovation among millennial employees.